Autologous Fat Grafting Promotes Macrophage Infiltration to Increase Secretion of Growth Factors and Revascularization, Thereby Treating Diabetic Rat Skin Defect - Wang Y (Dove Medical Press, 2020)
Yu Wang, Hao Zhang, Min Zhou, Xinzeyu Yi, Ping Duan, Aixi Yu, Baiwen Qi Department of Orthopaedic Trauma and Microsurgery, Wuhan University Zhongnan Hospital, Wuhan, Hubei 430071, People’s Republic of ChinaCorrespondence: Aixi Yu; Baiwen QiWuhan University Zhongnan Hospital, 169 East Lake Road, Wuchang District, Wuhan, Hubei 430071, People’s Republic of ChinaTel/Fax +86 67813120Email yuaixi@whu.edu.cn; wb002162@whu.edu.cnBackground: Diabetic skin defect is difficult to manage in surgical clinics, and there is still lack of effective treatments for diabetic skin defects. Currently, autologous fat grafting (AFG) is promising in the field of reconstructive surgery, while macrophage infiltration in autologous adipose tissue is considered vital for tissue regeneration. But AFG is rarely applied to the treatment of diabetic skin defects, and whether macrophage infiltration assists AFG to promote wound healing is still unknown.Methods: Full-thickness skin defect diabetic rats were divided into 3 groups: control group, autologous fat grafting (AFG) group and AFG with macrophage depletion (AFG+MD) group. We examined the amount of macrophages in the wounds bed and the expression level of inflammatory factors IL-10, IL-6, TNF-α, and also growth factors PDGF-β, TGF-β, IGF-1 at the same time. The content of collagen-I and α-smooth muscle actin protein in the wounds were determined by Western blot analysis. Finally, the healing of the wounds was evaluated.Results: The AFG group showing more rapid healing, secreting more growth factors and more obvious vascularization in the healing process, compared with the control group. But, the secretion of growth factors and the construction of extracellular matrix (ECM) in the wounds were limited when macrophages were depleted after AFG.Conclusion: AFG promotes the infiltration of macrophages to improve the healing environment of diabetic wounds by increasing the secretion of growth factors and revascularization, which provides a potential method for the treatment of diabetic skin defects.Keywords: diabetic skin defects, autologous fat grafting, wound healing, macrophage depletion